2023
DOI: 10.3847/1538-4357/ad03eb
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Heating and Solar Wind Generation by Flux Cancellation Reconnection

D. I. Pontin,
E. R. Priest,
L. P. Chitta
et al.

Abstract: In this paper, we propose that flux cancellation on small granular scales (≲1000 km) ubiquitously drives reconnection at a multitude of sites in the low solar atmosphere, contributing to chromospheric/coronal heating and the generation of the solar wind. We analyze the energy conversion in these small-scale flux cancellation events using both analytical models and three-dimensional, resistive magnetohydrodynamic (MHD) simulations. The analytical models—in combination with the latest estimates of flux cancellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Both models have since been refined and extended by, e.g., Oughton et al (2001), Dmitruk et al (2001Dmitruk et al ( , 2002, Suzuki & Inutsuka (2005), Cranmer et al (2007Cranmer et al ( , 2013, Cranmer & van Ballegooijen (2010), Wang et al (2009), Chandran & Hollweg (2009), Verdini et al (2010), Matsumoto & Shibata (2010), Chandran et al (2011), Usmanov et al (2011Usmanov et al ( , 2014, Lionello et al (2014), Woolsey & Cranmer (2014), Shoda et al (2018), Chandran & Perez (2019), and Chandran (2021) for Alfvén wave or slab turbulence heating and driving, and by Zank et al (2021), Adhikari et al (2020Adhikari et al ( , 2022, Telloni et al (2022aTelloni et al ( , 2022bTelloni et al ( , 2023 for 2D nonlinear structures. PSP observations (Bale et al 2023;Raouafi et al 2023), Solar Dynamics Observatory spacecraft observations (Uritsky et al 2023), and theory (Priest et al 2018;Zank et al 2018;Pontin et al 2024) have identified small-and multiscale magnetic reconnection low in the corona as a possible mechanism for solar coronal heating. Such small-and multiscale reconnection can be expected to generate slab (Matthaeus 1999), 2D (Zank et al 2018), or an admixture of MHD turbulence low in the corona.…”
Section: Introductionmentioning
confidence: 99%
“…Both models have since been refined and extended by, e.g., Oughton et al (2001), Dmitruk et al (2001Dmitruk et al ( , 2002, Suzuki & Inutsuka (2005), Cranmer et al (2007Cranmer et al ( , 2013, Cranmer & van Ballegooijen (2010), Wang et al (2009), Chandran & Hollweg (2009), Verdini et al (2010), Matsumoto & Shibata (2010), Chandran et al (2011), Usmanov et al (2011Usmanov et al ( , 2014, Lionello et al (2014), Woolsey & Cranmer (2014), Shoda et al (2018), Chandran & Perez (2019), and Chandran (2021) for Alfvén wave or slab turbulence heating and driving, and by Zank et al (2021), Adhikari et al (2020Adhikari et al ( , 2022, Telloni et al (2022aTelloni et al ( , 2022bTelloni et al ( , 2023 for 2D nonlinear structures. PSP observations (Bale et al 2023;Raouafi et al 2023), Solar Dynamics Observatory spacecraft observations (Uritsky et al 2023), and theory (Priest et al 2018;Zank et al 2018;Pontin et al 2024) have identified small-and multiscale magnetic reconnection low in the corona as a possible mechanism for solar coronal heating. Such small-and multiscale reconnection can be expected to generate slab (Matthaeus 1999), 2D (Zank et al 2018), or an admixture of MHD turbulence low in the corona.…”
Section: Introductionmentioning
confidence: 99%